Overexpression and Biochemical Properties of a GH46 Chitosanase From Marine Streptomyces hygroscopicus R1 Suitable for Chitosan Oligosaccharides Preparation - Wang, Jianrong; Wang, Ping; Zhu, Mujin; Chen, Wei; Yu, Si; Zhong, Bin (Frontiers in Microbiology, 2022)
Chitooligosaccharides (COSs) with various biological activities have great potential value of application in many areas. Chitosanase plays an important role on enzymatic preparation of COSs. Herein, a gene encoding a novel chitosanase (ShCsn46) from marine Streptomyces hygroscopicus R1 was cloned, optimized based on the codon usage of Pichia pastoris (P. pastoris), ligated to pPICZαA and overexpressed in P. pastoris X33. The maximum activity and total protein concentration of ShCsn46 were 2250 U/ml and 3.98 g/l, respectively. The optimal pH and temperature of purified ShCsn46 were 5.5 and 55°C, respectively. Meanwhile, ShCsn46 was stable from pH 5.0 to10.0 and 40 to 55°C, respectively. Besides, the purified ShCsn46 was obviously activated by Mn2+ and inhibited by Cu2+, Fe2+ and Al3+. In addition, substrate specificity of the purified ShCsn46 showed highest activity toward colloidal chitosan with 95% degrees of deacetylation. Furthermore, the purified ShCsn46 exhibited high efficiency to hydrolyze 4% colloidal chitosan and the hydrolysis rate reached 91.2% after 20 minute reaction. This study provides a novel chitosanase for the controllable preparation of COSs with desirable degrees of polymerization.